Making sense of the Web: a metaphorical approach - Lee Ratzan (Information Research: An International Electronic Journal)
The nature of the World Wide Web is unfamiliar to most people. In order to make sense of this foreign environment people describe the unfamiliar in terms of the familiar. Metaphors are often used for this purpose. Since it is important to use the Web effectively it is important to acquire insight on user perceptions. Preliminary results of the Internet Metaphor Project are presented.